How I Approach Leishmaniasis: Diagnosis and Treatment in the United States. Issue 11 (31st August 2022) - Ness, Tara E; Martin-Blais, Rachel; Weatherhead, Jill E
Abstract: Leishmaniasis is a vector-borne disease caused by over 20 species of obligate intracellular protozoa belonging to the genus Leishmania . Leishmaniasis has a global distribution, including in the United States, and can cause a spectrum of clinical syndromes, including cutaneous, mucosal, and visceral diseases depending on host factors and the infecting Leishmania spp. Accurate diagnosis, including Leishmania species identification, is an important step to guide the most appropriate therapeutic intervention. Antileishmanial therapy is dependent on the Leishmania spp. identified, the clinical syndrome, and the child's immune system. However, many treatment regimens for children have been extrapolated from adult clinical trials, which may lead to underdosing and subsequent poor outcomes in infected children. Additional research is urgently needed to help guide therapy for children and determine appropriate antileishmanial agents, doses, and treatment courses for children with leishmaniasis.